2007
DOI: 10.1080/13561820701722634
|View full text |Cite
|
Sign up to set email alerts
|

Therapists' experiences and perceptions of teamwork in neurological rehabilitation: Critical happenings in effective and ineffective teamwork

Abstract: This article reports the second part of an exploratory study into occupational therapists` and physiotherapists` perceptions and experiences of team-work in neurological rehabilitation: the factors that were thought to influence effective and ineffective team-work, and the meaning behind 3 effective and ineffective team work in neurological rehabilitation. The study was undertaken through semi-structured interviews of 10 therapists from three different neurological rehabilitation teams based in the United King… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 33 publications
2
23
0
1
Order By: Relevance
“…Our results are consistent with previous reports on differences between judgments of the clinical team and patients or their caregivers on restrictions of functioning (Brott et al, 1989;Glazier et al, 2004;Suddick and De Souza, 2007;Levack et al, 2009;Williams and Dahl, 2012). This inconsistency can be explained by the fact that stroke survivors may have neuropsychological deficits affecting the judgment of the severity of their condition (Suddick and De Souza, 2007).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with previous reports on differences between judgments of the clinical team and patients or their caregivers on restrictions of functioning (Brott et al, 1989;Glazier et al, 2004;Suddick and De Souza, 2007;Levack et al, 2009;Williams and Dahl, 2012). This inconsistency can be explained by the fact that stroke survivors may have neuropsychological deficits affecting the judgment of the severity of their condition (Suddick and De Souza, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…The highest possible degree of agreement between rehabilitation professionals and rehabilitants along with their families is one of the most important keys to successful rehabilitation (Neumann et al, 2010). In previous studies, this degree has been found to vary (Brott et al, 1989;Glazier et al, 2004), showing that neurologic patients and clinical team members do not necessarily agree on either limitations in functioning or specific goals for rehabilitation (Suddick and De Souza, 2007). Similar disagreement has been found between stroke patients and their caregivers (Williams and Dahl, 2012) as well as between caregivers and rehabilitation professionals (Levack et al, 2009).…”
Section: Introductionmentioning
confidence: 61%
“…There was some evidence to indicate this was influenced by the presence of a stable workforce with knowledge, skills and experience gained from previous work in rehabilitation stroke units, as reported in other studies [42][43][44] .…”
Section: Discussionmentioning
confidence: 53%
“…Physiotherapists and occupational therapists that often "co-treat" are required to establish an effective communication basis and coordination of care with joint responsibility for outcomes 30 . A study by Suddick et al (2007) that may have implications in this study found that the type of communication that could facilitate effective teamwork included having regular meetings, updates, discussions with team members and communicating with the patient and family 31 .…”
Section: Discussionmentioning
confidence: 99%